ASSESMENT OF POLY CYCYLIC AROMATIC HYDROCARBON (PAH) DISTRIBUTION IN DRY SEASON OF AMBIENT AIR OF OIL PRODUCING COMMUNITIES OF EGBEMA, IMO STATE, NIGERIA. - G.C. Anyanwu; Ohaeri, E. O. (IJRDO-Journal of Applied Science, 2022)
Mosses plants (pleurozium schreberi) was used to trap Poly cyclic aromatic hydrocarbon in ambient air of oil producing areas of Egbema, where the distribution and assessment of pollution in ambient air from six locations where harvested for Six months (Dry Season). Gas chromatography was used to analyze the samples where the mean average of PAH recorded Pyrene with highest concentrations of 9.74(µg/kg) followed by Fluoranthane with 4.50(µg/kg). Lowest concentration was Indeno(123)perylene with 0.13(µg/kg) while locations that recorded highest were AQOWH, AQEOJ with 2.86(µg/kg) followed by AQEWH and AQEWFS with 1.73(µg/kg) and 1.87(µg/kg) respectively. AQEOJ and AQOWH have largest variation spread of PAH in all locations, while Fluorathene recorded highest variation spread in all Locations. This research is used to ascertain the level of concentration of Polycyclic Aromatic Hydrocarbon during the dry season in various locations of Oil producing communities using a Bio indicator (pleurozium schreberi), and to understand the variability of natural environmental conditions and, at the same time, a significant diversity of anthropogenic influences in air quality of Egbema Oil producing communities in Imo State.It is also noted that not only oil exploration generates PAH spread in Egbema, there are other vices that contribute to daily exposures of PAH which is associated with increased incidences of premature death, chronic asthma and as well as respiratory problems in children.